Dabrafenib and trametinib in BRAFV600E mutated glioma. (October 2017) - Brown, Nicholas F; Carter, Thomas; Kitchen, Neil; Mulholland, Paul
BRAFV600E mutations have been identified in a number of glioma subtypes, most frequently in pleomorphic xanthoastrocytoma, ganglioglioma, pilocytic astrocytoma, and epithelioid glioblastoma. Although the development of BRAF inhibitors has dramatically improved the clinical outcome for patients with BRAFV600E mutant tumors, resistance develops in a majority of patients due to reactivation of the MAPK pathway. Addition of MEK inhibition to BRAF inhibition improves survival. Here we report successful treatment of two patients with BRAFV600E mutant pleomorphic xanthoastrocytoma using the BRAF inhibitor dabrafenib in combination with the MEK inhibitor trametinib.